La poesia popular i la Renaixença - Massot i Muntaner, Josep (Caplletra. Revista Internacional de Filologia, 2015)
From the second third of the 19th century onward, interest in anonymous oral literature grew in Catalan-speaking lands, which led people to collect, study, and imitate it.